Penggunaan Lumpur Sawit Kering (Dried Palm Oil Sludge) dan Serat Sawit (Palm Press Fiber) dalam Ransum Pertumbuhan Sapi Perah - Fauzia Agustin; T. Sutardi; D. Sastradipradja; J. Jachja (Buletin Ilmu Makanan Ternak, 1991)
An experiment was conducted to evaluate substitution of native grass and rice bran eith palm press fiber (PPF) and dried palm oil sludge (POS) in nine growing males dairy cattle. The animal had a mean of liveweight of 190 ± 11.2 kg. Levels of substitution were 0, 50, and 100% or 0, 15, and 30% of ration dry matter.Inclusion of PPF and POS in ration had no effect on daily liveweight gain (1.270 ± 0.2 kg). Analysis of empty body composition using the urea space technique revealed that the liveweight gain was associated with deposition of protein and fat. PPF had a low palatability and reduced total dry matter intake when the inclusion was higher than 7% of ration dry matter. However, the PPF was fermentable and volatile fatty acids (VFA) concentration in the rumen increased linearly as PPF level increased in the ration (VFA = 75 ± 0.53 PPF; P<0.05). The intake of the digested organic matter was 2.63, 2.68, and 1.97 kg and that of digestible energy was 19.3, 19.5 and 15.5 Mcal for ration caontaining 0, 15, 30% of PPF, respectively.It was concluded that the POS was an excellent substitute for rice bran, but PPF as a grass substitute should be limited up to 23% of total grass dry matter or 7% of ration dry matter.